Post publication peer review in Iranian biomedical journals: - Derakhshan Rad, Seyed-Alireza; Ghanbari, Ali (Galen Medical Journal, 2015)
Background: letters to the editor provide an opportunity for readers to state their views about published articles. Research on this issue has been mainly on western journals and there is no study on the Iranian journals. The present study aimed to investigate this subject in Iranian biomedical journals. Materials and Method: This was a bibliometric study. The databases of Iran Medex, Medlib, and SID were searched to find the letters published in Iranian biomedical journals. The letters in formats such as commentaries, concise articles, and the preliminary results of studies or brief reports were excluded from the study. Results: 184 letters were found in Iranian journals; 49 of them were responses of authors to the criticism made by readers. As a result, the number of letters that commented on or criticized the original articles reduced to 135. For every 1198 articles published in Iranian journals, there is only one letter written in correspondence to published articles. 76% of letters published in 2010 to 2012. Conclusions: the Iranian readers are much less productive in writing letters to Iranian biomedical journals compared to their peers in other places. The low number of letters could be attributed to several issues including a broad unawareness of the importance of the letters and little incentive for writing letter.The sharp rise in the number of letters after 2009 indicates a boosted motivation of Iranians for writing more letters to the editor.